Panel data on the impact of foreign direct investment and good governance on economic growth in the AMU countries – P-ARDL approache - Moussouni, Habiba (Management and Entrepreneurship: Trends of Development, 2024)
The advancement and well-being of a nation are closely linked to its economic growth, which serves as a key indicator of the nation's stability and strength. This stability is influenced by a variety of economic and non-economic factors. Among the economic factors, foreign direct investment plays a crucial role in enhancing the GDP, acting as a catalyst for competition and innovation. Conversely, non-economic factors significantly contribute to growth in an indirect manner. The AMU nations, classified as developing countries, experience challenges related to low and unstable GDP levels. Consequently, these countries are actively pursuing strategies to attract substantial foreign direct investment. It is essential to investigate the primary economic and non-economic factors that influence GDP growth. To analyze these factors and their effects on the GDP rates of the Maghreb countries, a Panel Data methodology was employed, utilizing a time series of seven control variables to control their effects on economic growth, covering the period from 1996 to 2022. The findings indicated a direct relationship and a long-term connection between controls variables and the dependent variable. Furthermore, the error correction term was found to be significant and negative (-1.091), suggesting that each year, 109.1% of the discrepancies in economic growth will be rectified over the long term. Based on the study's outcomes, it is evident that the Maghreb countries face significant challenges related to high corruption rates and political instability; thus, it is imperative for them to concentrate on these two indicators by implementing control mechanisms that promote transparency, ultimately enhancing the investment climate. JEL Classification: E42, E44, G34, F40